Future scenarios for Fast-Moving Consumer Goods in a circular economy - Kuzmina, Ksenija; Prendeville, Sharon; Walker, Dale; Charnley, Fiona (Elsevier, 2018)
The aim of the study is to envision, through an inductive scenario planning methodology, future scenarios of the fast-moving consumer goods (FMCG) industry in the context of a circular economy (CE). The study uses an exploratory scenario planning, an inductive approach to engage FMCG industry organisations, CE experts, end-users, and academic stakeholders in exploring the future of FMCG within a CE context. Five future scenarios that can inform a vision for the future of the FMCG industry were developed: (1) Rinse and Reuse, (2) The Cycling of Pure Materials, (3) The Rise of the Circular Retailer, (4) A World Without Supermarkets and (5) Connected Living. The analysis and discussion of the scenarios consider how value is created within circular economy and the integral role that the consumer and the IT play within it. The study provides insights on how the FMCG sector might participate in the CE and in doing so provides a basis for further research in this area. Future areas for research are outlined.
Keywords: Circular Economy; Fast-Moving Consumer Goods; Consumers; Scenarios